Voices of refugee children in Korea. (November 2018) - Nho, Choong Rai; Yoon, Sukyoung; Ko, Juae
Abstract: Little is known about refugee children in Korea, making it challenging to work with this population for social work and human service agencies. Employing thematic analysis method for individual in-depth and focus group interviews, this study examined difficulties of refugee children's past in their mother land, refugee camps (pre-displacement) and current experiences in Korea (post-migration) to draw implications for social work policy and practices. Five children for individual in-depth interviews and 10 children (five each from two separate ethnic groups) for focus group interviews were recruited. Their ages were between 9 and 18 years. Five main themes emerged: chaos, daily hassles, changed life, helping hands, and dreams along with their displacement process. This study addresses partnership between the Korean government and private agencies to meet basic and psychosocial needs of refugee children based on United Nations Convention on the Rights of the Child.